(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Blood glucose disorders, including hypoglycemia and hyperglycemia, are common metabolic complications in low birth weight neonates. This study aimed to determine the prevalence of glucose disorders in neonates under 2500g admitted to the Neonatal ICU at Children’s Hospital 2, and explore clinical associations. Subjects and Methods: A cross-sectional study was conducted from March to September 2024 on neonates weighing < 2500g admitted to the NICU. Capillary blood glucose was measured at admission and every 2 hours if abnormal. Clinical and epidemiological data were collected and analyzed. Results: Among 142 neonates, 37 (26%) had glucose disorders: 10 (7%) hypoglycemia and 27 (19%) hyperglycemia. The median time for normalization was 2 hours. No statistically significant association was found with clinical or epidemiological factors. Conclusion: Blood glucose disorders, especially hyperglycemia, are common in low birth weight neonates upon admission. Early glucose screening plays an essential role in timely diagnosis and treatment.